2016
DOI: 10.1016/j.afos.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Locomotive syndrome presents a risk for falls and fractures in the elderly Japanese population

Abstract: “Locomotive syndrome” is used to designate the condition of individuals with musculoskeletal disease who are highly likely to require nursing care. This article reviews screening, prevalence, causal and related factors, and the relationship between locomotive syndrome and falls and fractures in older adults with this syndrome. A few self-administered questionnaire tools are available to assess individuals for locomotive syndrome. Additionally, screening methods, including a physical functioning assessment, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
(87 reference statements)
2
20
0
7
Order By: Relevance
“…A reduction in muscle mass can lead to loss of motor control as a consequence of impaired muscle function control, and support of joint motions required to avoid falls during postural gravitational changes and reflexion. A decline of locomotive function was related closely with fall history, and accordingly sarcopenia was considered to be a major component of LS . In fact, the present study showed the percentage of LS was higher in fallers .…”
Section: Discussionsupporting
confidence: 47%
“…A reduction in muscle mass can lead to loss of motor control as a consequence of impaired muscle function control, and support of joint motions required to avoid falls during postural gravitational changes and reflexion. A decline of locomotive function was related closely with fall history, and accordingly sarcopenia was considered to be a major component of LS . In fact, the present study showed the percentage of LS was higher in fallers .…”
Section: Discussionsupporting
confidence: 47%
“…The terms of frailty and locomotive syndrome are similar, but locomotive syndrome is specified as physical frailty with musculoskeletal disease without social or cognitive frailty ( Fig. 1) [13]. The associations among full performance (health), frailty and disability are shown in Fig.…”
Section: Healthy Life Expectancymentioning
confidence: 99%
“…Recent geriatric syndrome studies addressed a number of complex conditions associated with aging, such as depression, frailty [14], sarcopenia [15], and locomotive syndrome [16], while several studies focused on motor functions [17][18][19][20][21]. One study reported that community-dwelling frail older adults are at high risk of depression [22].…”
Section: Introductionmentioning
confidence: 99%